Which infants with eczema are at risk of food allergy? Results from a population‐based cohort. Issue 1 (January 2015) - Martin, P. E.; Eckert, J. K.; Koplin, J. J.; Lowe, A. J.; Gurrin, L. C.; Dharmage, S. C.; Vuillermin, P.; Tang, M. L. K.; Ponsonby, A.‐L.; Matheson, M.; Hill, D. J.; Allen, K. J.; et al.
Summary Background The relationship between early onset eczema and food allergy among infants has never been examined in a population‐based sample using the gold standard for diagnosis, oral food challenge. Objective We characterised the risk of challenge‐proven food allergy among infants with eczema in the general population. Methods One‐year‐old infants (n = 4453 meeting criteria for this analysis) were assessed for history of eczema, received a nurse‐administered eczema examination and underwent skin prick testing to peanut, egg and sesame. Those with a detectable wheal to one of the test foods underwent an oral food challenge irrespective of wheal size. The risk of food allergy, stratified by eczema severity and age of onset, was estimated using multivariate logistic regression with population sampling weights. Results One in five infants with eczema were allergic to peanut, egg white or sesame, compared to one in twenty‐five infants without eczema (OR 6.2, 95% CI 4.9, 7.9, P < 0.001). The prevalence of peanut allergy was low in the absence of eczema (0.7% 95% CI 0.4, 1.1). Infants with eczema were 11.0 times more likely to develop peanut allergy (95% CI 6.6, 18.6) and 5.8 times more likely to develop egg allergy (95% CI 4.6, 7.4) by 12 months than infants without eczema. 50.8% of infants (95% CI 42.8, 58.9) with early eczema onset (<3 months) who required doctor‐prescribed topical corticosteroid treatment developed challenge‐proven food allergy. Conclusion and Clinical Relevance Eczema, across the clinical severity spectrum in infancy, is a strong risk factor for IgE‐mediated food allergy. Infants with eczema were six times more likely to have egg allergy and 11 times more likely to have peanut allergy by 12 months than infants without eczema. Our data suggest that a heightened awareness of food allergy risk among healthcare practitioners treating infants with eczema, especially if early onset and severe, is warranted.